Pengaruh Media Pembelajaran Berbasis Video Terhadap Hasil Belajar Siswa - Erni Fatmawati; Karmin; Rahayu Sri Sulistiyawati (Universitas Pancasakti Tegal, 2018)
The objectives of this research are to know: 1) Average learning outcomes of control class students; 2) Average learning outcomes of experimental class students; 3) The average difference between the students' control and experimental class learning outcomes. Experimental research method, with nonequivalent control group design. Sampling using purposive sampling amounted to 50 students. Techniques and data collection tools using measurement techniques in the form of test results learning. Data analysis using descriptive and inferential analysis. The results showed: 1) Average learning outcomes of control class students 72.93 good category. 2) Average learning outcomes of students of the experimental class of 79.87 categories is very good. 3) The difference of the average of control class learning outcomes with the experimental class using the t-test statistical test is Separated Variance obtained tcount = 5.932 and ttable = 2.064 with a significant level of 0.05. Then it can be concluded that there is difference of mean of result of learning of student of control class with experiment class.